ANALISIS PERKEMBANGAN SOSIAL ANAK TUNARUNGU USIA 4-5 TAHUN TK ALIFA KIDS 6 PEKANBARU - Sherly Damayanti (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2017)
This study aims to obtain data about the social development of deaf children in interacting with other people and their ability to communicate in the Alifa Kids 6 Kindergarten school Pekanbaru. In the social environment, verbal / oral communication is the most common form of communication. Meanwhile, in the case of deaf children, verbal communication is something that is difficult. In other words, children with hearing loss as a result of their hearing loss are hampered by the potential for developing language / speech skills. This research uses descriptive qualitative research. The research approach used in this research is qualitative research. The object in this study is the social interactions carried out by deaf children aged 4-5 class B. Based on the results of the study, it shows that deaf children Social contacts and communication between deaf children and normal children will affect the child's development. Normal children will learn to accept the shortcomings of friends and children with hearing impairment will learn how to adjust and grow the confidence to make friends with normal friends.